The collective action dilemma and its solution in the governance of urban community public space—an empirical analysis from Tianjin - Li, Yapeng (Frontiers in Built Environment, 2024)
The governance of community public space is one of the most concerned issue of people's livelihood, and its effectiveness determines the residents' living experience and even the stability of the grassroots political authority. In order to explore the factors of the effectiveness of community public space governance and the path to enhance the effectiveness of community public space governance, this analysis combines the influencing factors with the three stages of identification, management and confirmation in public value management theory, and constructs an indicator system for measuring and analyzing the effectiveness of community public space governance. The fsQCA3.0 is used to analyze the data of 300 residents in Tianjin, China, after which several aims that affect the effectiveness of community public space governance are obtained. The results show that the paths of "resident trust, property management is authoritative " and "customer oriented, democratic consultation" that bring higher governance efficiency have a consistency of 0.874761 and a coverage of 0.480994, which explains well what combination of antecedent factors should be present in communities with high public space governance effectiveness. Based on this, in order to improve the governance efficiency of community public space, improving residents' living experience and promote the modernization of China's urban construction, the government, property management company, owners' committee and neighborhood committee should increase investment in enhancing policy support, establishing service concepts, introducing technology and equipment, enhancing residents' trust and establishing dispute coordination agencies.